Mineralization of the Peritoneum — a New Target in the Treatment of Peritoneal Carcinomatosis - Sh. Kh. Gantsev; V. M. Moiseenko; K. Sh. Gantsev; S. V. Solomenny; Sh. R. Kzyrgalin; V. A. Dokichev; F. V. Moiseenko; R. S. Minigazimov (Креативная хирургия и онкология, 2019)
Introduction. This article presents data on the manifestations of changes in the microenvironment of the peritoneal cavity in patients with carcinomatosis, expressed by the mineralization of the peritoneum, which in turn leads to functional changes in drainage of the peritoneal cavity.Materials and methods. We examined autopsy tissue of the peritoneum with symptoms of carcinomatosis and intact peritoneum using comparative scanning electron microscopy.Results and discussion. The study of the ultrastructure of peritoneum in patients with PC, revealed the phenomenon of SLL mineralization. The resulting elemental composition profile showed a high content of Ca, P, Na.Conclusions. 1. Carcinomatosis is not a local, but rather a systemic process. Determining the role of mineralization in carcinomatosis is of fundamental importance in carcinogenesis. 2. The serous membranes mineralization in patients with carcinomatosis can become a new treatment target, the impact on which may increase life expectancy and improve the quality of life. 3. The serous membranes demineralization can serve as a part of a combination treatment that includes the subsequent endolymphatic anti-tumour drug therapy.